Well-being in cities and regions: Measurement, analysis and policy practices - Paolo Veneri; Arjen J. E. Edzes (REGION, 2017)
This note introduces the special issue on Well-being in cities and regions: measurement, analysis and policy practices. After highlighting the importance of well-being research, this contribution provides a rationale for focusing on the local level rather than looking at country averages for both analytical and policy purposes. While introducing the papers in this Special Issue, we highlight the need to focus on the regional and local factors that improve people's well-being and the need to understand the link between objective and subjective measures of well-being so that better use is made of them in policy making.
Keywords: 330; Well-being; Cities; Regions; Special Issue